Tetrapod species–area relationships across the Cretaceous–Paleogene mass extinction - Roger Adam Close; Bouwe Rutger Reijenga (Proceedings of the National Academy of Sciences, 2025)
Mass extinctions are rare but catastrophic events that profoundly disrupt biodiversity. Widely accepted consequences of mass extinctions, such as biodiversity loss and the appearance of temporary “disaster taxa,” imply that species–area relationships (SARs, or how biodiversity scales with area) should change dramatically across these events: Specifically, both the slope (the rate of accumulation of new species with increasing area) and intercept (the density of species at local scales) of the power–law relationship should decrease. However, these hypotheses have not been tested, and the contribution of variation in the SAR to diversity dynamics in deep time has been neglected. We use fossil data to quantify nested SARs in North American terrestrial tetrapods through the Cretaceous–Paleogene (K/Pg) mass extinction (Campanian–Ypresian). We show that SARs vary substantially through time and among groups. In the pre-extinction interval (Maastrichtian), unusually shallow SAR slopes (indicating low beta diversity or provinciality) drive low total regional diversity in dinosaurs, mammals, and other tetrapods. In the immediate postextinction interval (Danian), the explosive diversification of mammals drove high regional diversity via a large increase in SAR slope (indicating higher beta diversity or provinciality), and only a limited increase in SAR intercept. This contradicts the expectation that postextinction biotas should be regionally homogenized by the spread of disaster taxa and impoverished by diversity loss. This early postextinction increase in SAR slope was followed in the Thanetian–Selandian ( ∼ 4.4. myr later) by increases in the intercept, indicating that diversity dynamics at local and regional scales did not change in synchrony.